Increased urinary excretion of thioether in new rubber workers - Kilpikari, I (1982)
ABSTRACT Urinary excretion of thioether before starting work and in the early work period in a rubber factory was measured in urine samples collected after one, two to four, and five or more months of starting work. The study population consisted of 84 new workers. The urinary excretion of thioether decreased after one month's exposure and increased thereafter up to five months. Measurement of urinary thioethers in groups of new workers is therefore informative of exposure to alkylating agents only after several months from starting work. This effect may be mediated by the induction of the pertinent metabolic pathway.